1991
DOI: 10.1021/bi00217a027
|View full text |Cite
|
Sign up to set email alerts
|

Laser flash photolysis studies of the reduction kinetics of NADPH:cytochrome P-450 reductase

Abstract: The reduction kinetics of NADPH:cytochrome P-450 reductase have been investigated by the laser flash photolysis technique, using the semiquinone of 5-deazariboflavin (5-dRfH.) as the reductant. Transients observed at 470 nm at neutral pH indicated that the oxidized reductase was reduced via second-order kinetics with a rate constant of 6.8 X 10(7) M-1 s-1. The second-order rate constant corresponding to the formation of the protein-bound semiquinone (measured at 585 nm) was essentially the same as that obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
37
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 34 publications
10
37
0
Order By: Relevance
“…(ii) In early measurements of the stoichiometry of cytochrome c reduction [15] it was found that at least two thirds of the reducing equivalents were transferred from NADPH to cytochrome c with high rates under single turnover conditions, suggesting heterogeneity of the FMN semiquinone enzyme form, a fraction of which is catalytically competent. (iii) As shown by £ash photolysis [16] (Table 1), and is clearly not an intermediate of catalysis, but rather represents a sluggish enzyme form analogous to the inactive three-electron reduced £avoprotein of P450BM3 [5,19]. This`air-stable' semiquinone form of the enzyme is unable to rapidly reduce cytochrome c despite the fact that the reduction is thermodynamically favored by +350 mV.…”
Section: Discussionmentioning
confidence: 95%
“…(ii) In early measurements of the stoichiometry of cytochrome c reduction [15] it was found that at least two thirds of the reducing equivalents were transferred from NADPH to cytochrome c with high rates under single turnover conditions, suggesting heterogeneity of the FMN semiquinone enzyme form, a fraction of which is catalytically competent. (iii) As shown by £ash photolysis [16] (Table 1), and is clearly not an intermediate of catalysis, but rather represents a sluggish enzyme form analogous to the inactive three-electron reduced £avoprotein of P450BM3 [5,19]. This`air-stable' semiquinone form of the enzyme is unable to rapidly reduce cytochrome c despite the fact that the reduction is thermodynamically favored by +350 mV.…”
Section: Discussionmentioning
confidence: 95%
“…In the wild-type protein, there is a rapid (30 -70 s Ϫ1 ), reversible exchange of electrons between the two flavins (20,21). At equilibrium, the distribution of the electrons is governed by the redox potentials of the individual flavin half-reactions (FMN ox/sq ϭ Ϫ110 mV, FMN sq/hq ϭ Ϫ270 mV, FAD ox/sq ϭ Ϫ290 mV, and FAD sq/hq ϭ Ϫ365 mV) (7)(8)(9).…”
Section: ⌬Tgee Is Monomeric and Its Conformation Is Elongated In Solu-mentioning
confidence: 99%
“…Reaction 3 decreased 7-fold in ⌬TG (k ϭ 6.5 s Ϫ1 ) and 410-fold in ⌬TGEE (k ϭ 0.11 s Ϫ1 ) (Table 3A) (20,21).…”
Section: Two-electron Reduced ⌬Tgee Catalyzes Product Formation By Cymentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of CaM, this lock is removed, facilitating electron transfer between FAD and FMN. Intramolecular electron transfer between the two flavins in CPR has been studied using laser flash photolysis (31) and temperature-jump relaxation spectroscopy (32). Pulse radiolysis was used to study the electron transfer in nNOS (33).…”
mentioning
confidence: 99%